A Biophysical and Economic Assessment of a Community‐based Rehabilitated Gully in the Ethiopian Highlands. (20th October 2015) - Ayele, Getaneh K.; Gessess, Azalu A.; Addisie, Meseret B.; Tilahun, Seifu A.; Tebebu, Tigist Y.; Tenessa, Daregot B.; Langendoen, Eddy J.; Nicholson, Charles F.; Steenhuis, Tammo S.
Abstract: Gully erosion reduces agricultural productivity by destroying valuable land resources, increases sediment concentrations, reduces water quality, and fills up reservoirs. Gully rehabilitation has proven to be challenging especially in the high‐rainfall areas of the Ethiopian Highlands and has therefore had limited success. This paper describes a successful low‐cost gully rehabilitation effort with community participation in the Birr watershed in the Blue Nile basin that begun in early 2013. Initially, farmers were reluctant to participate for religious reasons, but with the aid of local priests and respected elders, community discussions, and a visit to a rehabilitated gully, a consensus was reached to rehabilitate a 0·71‐ha upland gully. The rehabilitation measures consisted of regrading the gully head at a 45° slope, constructing low‐cost check dams from locally available materials, and planting Pennisetum purpureum grass and Sesbania sesban . At the end of the first post‐implementation rainy season, 2, 200 tons of soil was conserved by the constructed check dams and newly planted vegetation, compared with soil losses of 680 and 560 tons in two untreated, nearby gullies. In 2014, an additional 3, 100 tons of soil was conserved. In 2013, the marginal rate of return (MRR) on the gully rehabilitation investment was 2·6 based on the value of increased forage production alone. When we include trapped soil nutrient values, the rehabilitation MRR was increased to 10. Although these numbers are impressive, the best proof of the success was that farmers on their own initiative rehabilitated an additional five gullies in 2014. Copyright © 2015 John Wiley & Sons, Ltd.